(untitled) (Journal of Geography and Environmental Management, 2017)
239, 240Pu is a long-lived radionuclide, the amount of which accumulates in natural ecosystems from incident to incident. The radiotoxicity of this radionuclide is high, and scientifically based approaches to the assessment and prediction of radioecological conditions of ecosystems at risk of 239, 240Pu radioactive contaminations are needed. In the present work, of the soil of Sarapan settlement for the presence of weapons-grade plutonium -239, 240 was made. It is known that the Sarapan settlement is located on the territory of the former STS, which is used by local residents for agricultural purposes. Soil samples were analyzed in the radioecological research laboratory of the Shakarim State University for the content of weapons-grade Pu-239,240 by the alpha-spectrometric method after preliminary radiochemical preparation. It has been established that the content of plutonium isotopes in the soil of Sarapan settlement is an average of 0,05+/-0,01 Bq / kg, which is slightly higher than the level of pollution caused by global fallout. The annual effective dose of irradiation from the soil of people living in this area, calculated by mathematical modeling, taking into account the metabolism of plutonium isotopes is 1.95 mSv / year.